Development of pole-changing windings for close pole ratio - Rismuxamedov, Dauletbek; Shamsutdinov, Husniddin (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: the industry of technologically developed countries produces various types of pumps, fans and compressors in quantities amounting to millions of pieces per еar. In our Republic, about 2,000 pumping stations are used annually during the growing season. In addition, large thermal stations, industrial enterprises, and agricultural facilities of the Republic are equipped with numerous pumps, fans and compressor units, the consumption of which exceeds 25% of all electricity generated by the country's energy systems. The high energy consumption of these objects gives great national economic significance to the problem of energy saving. As is known, energy saving in turbomechanisms is achieved by changing the number of revolutions of the drive motor. This increases the efficiency of the installation by an average of 20% compared to a non-adjustable electric drive, and also makes it easier to start the installation at a reduced rotation speed. Aim: development of pole-changing winding circuits with improved electromagnetic properties and simplified manufacturing technology with 108 stator slots for a pole pair ratio of 5/6. Methods: to develop circuits with a variable number of poles, the method of discrete spatial functions was used, including uniform distribution of currents across the stator slots. Results: by replacing two-speed motors with two separate windings with two-speed motors with one pole-changing winding, it is possible to reduce economic costs - up to 30 ÷ 40% for electrical steel, up to 40 ÷ 50% for winding copper and the labor intensity of winding production. In addition, the energy indicators such as efficiency and cos φ of the engine will increase by an average of 10 ÷ 15%. When replacing single-speed engines with two-speed ones, two fixed speeds can be obtained, which leads to an increase in efficiency (fan, pump, compressor, etc.) by an average of 20% and energy savings of up to 50% in operating modes with a lower load (seasonal or technological load change).